Effect of a Primary Care-Based Diabetes Education Model on Provider Referrals and Patient Participation. Issue 1 (February 2021) - Krall, Jodi S.; Kanter, Justin E.; Ruppert, Kristine M.; Arena, Vincent C.; Solano, Francis X.; Siminerio, Linda M.
Purpose: The purpose of this study was to evaluate the impact of a primary care (PC)-based delivery model on diabetes self-management education and support (DSMES) referrals and participation. Despite evidence that DSMES is a critical component of diabetes care, referrals and participation remain low. Methods: PC practices were assigned to the intervention (n = 6) or usual care (n = 6). Intervention practices had direct access to a diabetes educator (DE) and applied patient-centered medical home elements to DSMES delivery. Usual care practices referred patients to traditional hospital-based outpatient DSMES programs. DSMES referrals and participation were examined for patients with diabetes, 18 to 75 years old, presenting to PC over 18 months (n = 4, 894) and compared between groups. Results: Compared to the usual care group, a higher percentage of patients in the intervention practices were referred to DSMES (18.4% vs 13.4%; P < .0001), and of those referred, a higher percentage of patients in the intervention practices participated in DSMES (34.9% vs 26.1%; P = .02). Patient-level factors predicting referrals were obesity (odds ratio [OR] = 1.6), higher A1C (OR = 1.4), female (OR = 1.3), and younger age (OR = 0.98). The only patient-level factor that predicted DSMES participation was lower A1C (OR = 0.9). Conclusions: This study demonstrates the positive influence of a PC-based intervention on DSMES referral and participation. However, modest improvements in DSMES rates, even with targeted efforts to address reported barriers, raise questions as to what is truly needed to drive meaningful change.